Reconceptualising knowledge in the athlete–coach learning system: a mixed-method case study of harnessing bi-directional self-organising tendencies with a national wheelchair rugby league team - Rothwell, Martyn; Strafford, Ben William; Cragg, Scott; Ribeiro, João; Davids, Keith (Frontiers in Sports and Active Living, 2023)
Knowledge and knowledge transfer are often viewed in unitary and hierarchical terms, where a linear transaction exists between an individual possessing a body of knowledge and a person needing that knowledge. Although this traditional view of knowledge transfer is common within the sports domain, it is problematic because knowledge is treated as a self-contained entity. The overarching purpose of this study is to explore the ecological role of knowledge, underpinning performance preparation processes in an international coaching setting. Specifically, we investigated how bi-directional self-organising (coordination) tendencies (coach and athlete-led) can be exploited to facilitate the formation of attacking synergies within the team sport of wheelchair rugby league. A mixed-method case study approach was employed to collect data, involving semi-structured interviews, reflexive observations and field notes, and notational analysis. Results from the study described the transitional process of positioning an ecological view of knowledge transfer as a guiding principle to enhance athlete and practitioner collaboration. This reciprocal relationship provided documented opportunities to enhance on- and off-field team synergies. The pedagogical experiences we describe emerged throughout periods of uncertainty, requiring effortful interactions, forged on the continuous coupling of key agents (individuals), content, and context, enabling application, refinement, and opportunities for team synergies to evolve in performance preparation. Results suggested that the challenge of understanding and facilitating knowledge transfer could be embedded within the ecology of a complex adaptive system, sustained as a contextualised activity reciprocally constructed through on-going correspondence between athletes, scientists, practitioners, and the competitive performance context.